1998
DOI: 10.1111/j.1365-2621.1998.tb15822.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance by American and Asian Consumers of Extruded Fish and Peanut Snack Products

Abstract: Fish snack half-products were produced using extrusion temperatures and screw speeds of 97ЊC and 285 rpm, 95ЊC and 350 rpm, and 95ЊC and 220 rpm. Peanut snack half-products were produced at 100ЊC and 250 rpm, 95ЊC and 325 rpm, and 95ЊC and 250 rpm. The half-products were fried at 200ЊC for 1.5 min and evaluated for acceptability using a 9-point hedonic scale. Temperature and screw speed influenced consumer acceptance. Aroma, flavor, and overall acceptance of fish snack products were rated significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…The use of rice flour as an ingredient during extrusion cooking of protein products has significantly increased due to its unique attributes like bland taste, attractive white color, hypoallergenicity, and ease of digestion (Kadan et al 2003). The snacks based on fish and rice flour are gaining importance in Southeast Asian countries (Suknark et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of rice flour as an ingredient during extrusion cooking of protein products has significantly increased due to its unique attributes like bland taste, attractive white color, hypoallergenicity, and ease of digestion (Kadan et al 2003). The snacks based on fish and rice flour are gaining importance in Southeast Asian countries (Suknark et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A five-or seven-point hedonic scale is in general used to do the sensory analysis by either trained or semi-trained panelists. Suknark et al (1998) evaluated fish snacks produced at various combinations of barrel temperature and screw speed based on a nine-point hedonic scale for the product attributes like aroma, flavor, and overall acceptance of fish snack products. Stone et al (1974) evaluated fish samples using semistructured, quantitative description analysis and seven-point hedonic scale for attributes like flaky, firmness, dryness, chewy fibrous, and off-flavors.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies involving acceptance testing also found that the flavor influenced overall preference more than appearance, aroma or texture (Drake & Gerard, 2003;Drake, Truong, & Daubert, 1999;Melo et al, 2009;Palazzo & Bolini, 2009;Suknark, McWatters, & Phillips, 1998).…”
Section: Acceptance Testmentioning
confidence: 93%
“…Acceptability of noodles made from 98/0505 was supported by their good sensory scores on taste, flavour and texture. Texture has been described as one of the most important characteristics affecting consumer acceptance of snack products (Suknark et al 1998).…”
Section: Sensory Evaluationmentioning
confidence: 99%